Margaret of Austria, Visual Representation, and Brussels, Royal Library, Ms. 228 - Meconi, Honey (Journal of the Alamire Foundation, 2010)
Abstract Using as its starting point the miniature of Margaret of Austria in the manuscript Brussels, Royal Library, Ms. 228, the essay places this famous chansonnier in multiple contexts. After a brief bibliographic biography, it surveys manuscript images and diptych portrayals of Margaret, owner images and main openings within the Habsburg-Burgundian manuscript complex, and the other five chansonniers that Margaret owned. It shows that the Brussels 228 miniature is unique in almost all its components and that the manuscript represents a synthesis of her two earlier surviving chansonniers. Positioning the manuscript within aspects of her biography normally overlooked by musicologists, it shows both that the song texts would have acquired new meaning at the time of Brussels 228’s compilation and that the manuscript was an opening salvo in Margaret’s visual campaign to regain her lost status.